2002
DOI: 10.1094/pdis.2002.86.4.356
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Foliar Disease of Staked Fresh Market Tomatoes Grown Under Differing Bed Strategies

Abstract: The use of mulch or compost to reduce foliar disease in fresh market tomato could reduce fungicide use. Between 1997 and 1999, foliar disease was monitored in tomatoes grown in beds with bare soil, black polyethylene, composted dairy manure, or hairy vetch. Early blight was reduced in plots with vetch compared with bare soil or compost in all years and compared with polyethylene cover in 1 year. Early blight was reduced in plots with polyethylene versus compost and bare soil in 1 and 2 years, respectively. Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
4
23
0
1
Order By: Relevance
“…Trudan 8) cover crop was shown to reduce the splash dispersal of conidia of Colletotrichum acutatum Simmonds, the causal agent of anthracnose of strawberry (Ntahimpera et al 1998). Mills et al (2002) found that a decrease in tomato foliar diseases (early blight caused by A. solani, and Septoria leaf spot, caused by Septoria lycopersici) in a dead mulch of hairy vetch (Vicia villosa) was associated with reduced splash dispersal.…”
Section: Barrier Effects Against Pests and Pathogens At The Field Levelmentioning
confidence: 99%
“…Trudan 8) cover crop was shown to reduce the splash dispersal of conidia of Colletotrichum acutatum Simmonds, the causal agent of anthracnose of strawberry (Ntahimpera et al 1998). Mills et al (2002) found that a decrease in tomato foliar diseases (early blight caused by A. solani, and Septoria leaf spot, caused by Septoria lycopersici) in a dead mulch of hairy vetch (Vicia villosa) was associated with reduced splash dispersal.…”
Section: Barrier Effects Against Pests and Pathogens At The Field Levelmentioning
confidence: 99%
“…In very high chemical input systems, such as fresh market tomato production (4), the use of legume cover crops offers advantages as a biological alternative to commercial fertilizer (5) that reduces soil erosion and loss of nutrients (6), enhances water infiltration, reduces runoff, and creates a ''natural'' pestpredator relationship (7). An important economical outcome of legume cover crop use has been the stemming of disease incidence or severity in diverse crops (ref.…”
mentioning
confidence: 99%
“…Up-regulated genes included the most abundant chloroplast protein, ribulose bisphosphate carboxylase/oxygenase (Rubisco), important for carbon fixation; nitrogen-responsive glutamine synthase, regulating carbon/nitrogen signaling; nitrogen utilizing and nitrite toxicity reducing nitrite reductase; nitrogen-use efficiency protein glucose-6-phosphate dehydrogenase; chaperone proteins (HSP70 and ER protein BiP) that stabilize native proteins; cytokinin-and gibberellin-related regulatory proteins; and plant defense anti-fungal proteins chitinase and osmotin. Up-regulation of these plant defense genes may contribute to disease resistance as, in these and other field experiments, hairy vetch-grown tomato had less disease than tomato grown under black plastic [52,53,55].…”
Section: Impact Of Hairy Vetch Cropping System On Tomato Physiologymentioning
confidence: 72%
“…It was thought that more complete coverage of the soil surface with the hairy vetch mulch (hairy vetch mulch covers the entire field while black plastic covers the tomato beds but not the interspaced rows) physically obstructed splashed soil near the soil surface preventing soil infested with pathogen inoculum from entering the tomato canopy. The tomato crop grown in the hairy vetch mulch had negligible loss to early blight in the absence of fungicide relative to the fungicide treated controls [52,53]. There was also greater resistance of the tomato crop grown in the hairy vetch mulch to invasion and damage by the Colorado potato beetle [54].…”
Section: Next-generation Cover Crop-based Sustainable Tomato Productimentioning
confidence: 99%
See 1 more Smart Citation